The Risk of Pulmonary Embolism in Patients With Pemphigus: A Population-Based Large-Scale Longitudinal Study - Kridin, Khalaf; Kridin, Mouhammad; Amber, Kyle T.; Shalom, Guy; Comaneshter, Doron; Batat, Erez; Cohen, Arnon D. (Frontiers in Immunology, 2019)
Growing evidence suggests that inflammation may pose an atypical risk factor for pulmonary embolism (PE), as it drives venous thrombosis via several pathways. The increased risk of PE in several autoimmune diseases has lent weight to this concept. However, the relative risk of PE among patients with pemphigus has not yet been established. We aimed to examine the risk of PE in patients with pemphigus. A large-scale population-based longitudinal cohort study was conducted to evaluate the relative risk (RR) of PE among 1,985 patients with pemphigus relative to 9,874 age-, sex-, and ethnicity-matched control subjects. A multivariate Cox regression model was utilized. The incidence of PE was 3.0 (95% CI, 2.2-4.0) and 1.2 (95% CI, 1.0-1.5) per 1,000 person-years among patients with pemphigus and controls, respectively. The period prevalence of PE corresponding to the study period was 2.2% (95% CI, 1.6-2.9%) among cases and 0.9% (95% CI, 0.7-1.1%) among controls. Patients with pemphigus were twice as likely to develop PE as compared to control subjects (adjusted RR, 1.98; 95% confidence interval [CI], 1.29-3.04). The highest PE risk was observed during the first year following the diagnosis of pemphigus (adjusted RR, 3.55; 95% CI, 1.78-7.09) and decreased over time. The increased risk was robust to a sensitivity analysis that included only cases managed by pemphigus-related systemic medications (adjusted RR, 1.82; 95% CI, 1.11-2.98). In conclusion, pemphigus is associated with an increased risk of PE, particularly during the first year of the disease. An awareness of this risk should be increased, additional precipitating factors for PE should be avoided, and thromboprophylaxis may be evaluated in high-risk patients. Further research is required to establish this risk.